Heavy metal contamination and health risk assessment in drinking water of Sistan and Baluchistan, Southeastern Iran. Issue 8 (17th November 2017) - Mirzabeygi, Majid; Abbasnia, Abbas; Yunesian, Masoud; Nodehi, Ramin Nabizadeh; Yousefi, Nader; Hadi, Mahdi; Mahvi, Amir Hossein
ABSTRACT: Access to safe and clean drinking water is an essential element of healthy life also known as the primary human needs. The present study was conducted to investigate heavy metal (HM) concentrations of drinking water. Excess health risk of HM (Cr, Pb, and Cd) intake is related to the drinking water consumption in local population. HMs concentrations were analyzed by using graphite furnace atomic absorption spectrometer and were compared with permissible limits regulated by country and World Health Organization (WHO). The hazard quotient (HQ) and Excess Lifetime Cancer Risk (ELCR) were determined to show the carcinogenic and non-carcinogenic effects of HMs, respectively. HQs were found in the order of Pb > Cd > Cr and subsequently HI index was also estimated for all HM in two age groups (children and adults). The comparisons indicate no possibility of non-carcinogenic effects to the local population. The values for ELCR were found in the order of Cr > Cd > Pb. The ELCR index was found above acceptable risk levels for chromium and cadmium in both children and adults groups. Furthermore, intermetal correlation results revealed that heavy metals have common sources resulting from geogenic and anthropogenic activities and these are major sources of water contamination in Sistan and Baluchestan province.